FARMAKOGENOMIK: PENDEKATAN FARMAKOLOGI MENUJU PERSONALISED MEDICINE - Jefman Efendi Marzuki HY; Anggi Gayatri (Universitas Ciputra Surabaya, 2023)
One of the factors contributing to patient morbidity and death is variable variability in treatment response. Adverse drug responses (ADRs) or subtherapeutic effects are possible in certain patients during medication administration. The genetic variation is one of the many variables that contribute to this condition. Pharmacogenomics is the study of how genes influence an individual's response to drugs. The goal of pharmacogenomics is to optimise treatment for the patient. It has been established that a number of genes are associated with drug response, which affects both the direct effects of drugs (pharmacodynamics) and their blood levels (pharmacokinetics). Modifications to a medication's pharmacokinetics and pharmacodynamics may result in toxicity or lessen its efficacy. In order to increase the precision of pharmacotherapy techniques, this study aims to elucidate the availability of data on genetic variants that are known to affect medication response.